2009
DOI: 10.1159/000239761
|View full text |Cite
|
Sign up to set email alerts
|

Totally Laparoscopic Low Anterior Resection for Lower Rectal Cancer: Combination of a New Technique for Intracorporeal Anastomosis with Prolapsing Technique

Abstract: Background: Laparoscopically assisted low anterior resection is difficult even for experienced surgeons because of difficulties in selecting the appropriate transection line and completing anastomosis in the narrow pelvic space. The prolapsing technique resolves these problems. We combined our new technique for intracorporeal anastomosis with this prolapsing technique and achieved a totally laparoscopic low anterior resection. Methods: After the total mesorectal excision, a semi-circumferential colotomy is mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 20 publications
0
31
0
1
Order By: Relevance
“…45,46 One prospective study found no infection-related complications after transanal specimen extraction for diverticulitis despite positive polymicrobial peritoneal cultures. 47 Furthermore, anal sphincter function was not negatively impacted by transanal NOSE, 48,49 with patients reporting significant improvement in their quality of life at 6-month follow up. 50 Overall, based on these few non-randomized NOSE studies, transvaginal and transanal extraction of colorectal resection specimens appears to be safe, associated with reduced pain and shorter LOS, and offering at least the cosmetic benefit of eliminating extraction site incisions.…”
Section: Natural Orifice Specimen Extractionmentioning
confidence: 96%
“…45,46 One prospective study found no infection-related complications after transanal specimen extraction for diverticulitis despite positive polymicrobial peritoneal cultures. 47 Furthermore, anal sphincter function was not negatively impacted by transanal NOSE, 48,49 with patients reporting significant improvement in their quality of life at 6-month follow up. 50 Overall, based on these few non-randomized NOSE studies, transvaginal and transanal extraction of colorectal resection specimens appears to be safe, associated with reduced pain and shorter LOS, and offering at least the cosmetic benefit of eliminating extraction site incisions.…”
Section: Natural Orifice Specimen Extractionmentioning
confidence: 96%
“…Of 220 patients treated for low rectal cancer, 17 (8%) were stage 0 (pT0-N0, complete response after radiochemotherapy), 87 (40%) were stage I (pT1-2N0), 43 (20%) were stage II (pT3-4N0), and 73 (33%) were stage III (pT1-4N1-2). The tumor size was 3.5 cm (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The median number of lymph nodes analyzed was 13 (range, 1-40).…”
Section: Pathologic Data and Quality Of Surgerymentioning
confidence: 99%
“…6 One of the main restrictions for developing laparoscopic surgery in rectal cancer are the difficulties for stapling the distal rectum to achieve a low anterior resection. 8,9 This may translate to a higher rate of APR in laparoscopic procedures, 10 the necessity to use hybrid procedures for rectal transection 11 or to perform a hand-sewn coloanal anastomosis. There are few data of full laparoscopic coloanal anastomosis for rectal cancer, [12][13][14] including small series 12 and short follow-up.…”
mentioning
confidence: 99%
“…Furthermore, transanal pull-through, extracorporeal colectomy, and successful reestablishment of gastrointestinal continuity has been reported in a human study utilizing a different surgical technique. 19 Although more investigation is warranted, the totally laparoscopic NOTES-assisted procedure reported in this article has the potential to limit surgical complications associated with laparotomy and contamination by utilizing aseptic bowel manipulation during clean endolumenal colorectal resection and transanal specimen extraction without rectal stump opening or mini laparotomy. Furthermore, the IPT method may provide a clean conduit for bowel extraction as a part of existing, as well as future, minimally invasive NOSE techniques.…”
Section: Discussionmentioning
confidence: 98%